EFFECT OF PARTICLE SIZE AND CUTTING HEIGHT OF CORN (Zea mays L.) FOR SILAGE ONPRODUCTION PARAMETERS, VEGETATIVE COMPOSITION AND FEEDLOT PERFORMANCE OF STEERS - MIKAEL NEUMANN (Revista Brasileira de Milho e Sorgo, 2007)
The experiment was conducted at the Núcleo de Produção Animal (NUPRAN)of the Universidade Estadual do Centro Oeste do Paraná (UNICENTRO). The trial aimed to evaluate the effect of particle size (small: between 0.2 and 0.6 cm or large: between 1.0 and 2.0 cm) and cutting height (low cut: 15 cm or high cut: 39 cm) of the corn plant on agricultural value, vegetable composition and production costs of silages. The treatments were: T1 – small particle size with low cut height; T2 - large particle size with low cut height; T3 - small particle size with high cut height; and T4 - large particle size with high cut height. The low cut height system showed an increase (P<.05) of 7.1% on dry matter production compared to high cut height. Silage produced with the higher cut showed lower neutral detergent fiber content improving silage nutritional value. Raising the cutting height from 15.2 cm to 38.6 cm during silage processing, did not affect (P > 05) the animal performance in feedlot with roughage:concentrate ratio at 62.7:37.3. The silage with high cut and small particle size on feedlot resulted in higher (P< 05) production system lucrative.